An Application of Peer Tutoring to Improve Volleyball Bottom Passing Skills in Semester 1 Physical Education Students at Bengkulu University - Oddie Barnanda Rizky; Andika Prabowo; Andes Permadi; Septian Raibowo Raibowo; Arwin Arwin (Musamus Journal of Physical Education and Sport (MJPES), 2023)
Objectives. The study observed that some first-semester Physical Education students at Bengkulu University lacked proficiency in basic volleyball techniques such as passing and were not motivated by their lecturers' teaching methods. To address this, the peer tutorial method was applied to skilled students. This proved successful and saved time. The research aims to evaluate whether this method can improve passing skills. The study uses action research. Materials and Methods. The subjects of this research were 1st Semester Physical Education Students at Bengkulu University with a total of 30 students consisting of 17 men and 13 women. Data collection techniques were carried out using observation, and tests of volleyball passing skills. Results. Pre-cycle research found 56.67% students failed to understand bottom passing movement (17 students). Cycle I peer tutorial improved to 66.66% (19 students). Cycle II improved further to 76.67% (23 students). Conclusion. The results suggest that the peer tutorial method has a positive impact on improving volleyball bottom passing skills, resulting in an increase in the number of students passing the bottom.